Errors in Pronouncing the English Fricatives Found in the EFL Student’s Presentation videos: a contrastive analysis - Yusni, Putri Martessya; Zulfakhri , Zulfakhri (Linguistika Kultura, 2025)
This article discussed the pronunciation errors of English fricative consonants made by English Literature students of the 2019 at Universitas Andalas, as found in their thesis presentation videos. The aim of this thesis is to identify the types of pronunciation errors and analyze their causes by comparing the sound systems of English and Bahasa Indonesia. The research begins by selecting 20 students’ presentation videos as the data source. The focus is on English fricative consonants, specifically the sounds [f], [v], [θ, [ð], [s], [z], [ʃ], and [ʒ]. These sounds are transcribed from the videos and carefully analyzed. The research method used is descriptive qualitative, where the researcher applied contrastive analysis to understand the factors causing errors in pronunciation, including the influence of mother tongue interference and lack of knowledge of English. The theories used in this research were taken from April McMahon’s (2002) book entitled An Introduction to English Phonology, which is supported by the book Second Language Acquisition: An Introductory Course from Gass & Selinker (2008), and the book from Gut (2009) entitled Introduction to English Phonetics and Phonology, which help in understanding how second language learners acquire and pronounce unfamiliar sounds. Through this process, the researcher found that many students substitute fricative sounds with incorrect ones, especially [θ], [ð], [ʒ], and [ʃ]. The dominant type of pronunciation error is misformation error, where the students replace correct fricative sounds with native language alternatives. These errors were caused by interlingual transfer and intralingual transfer